Molecular Insights into Zn2+ Inhibition of the Antibacterial Endopeptidase Lysostaphin from Staphylococcus simulans - Chen, Ke; Ojha, Suvash C.; Imtong, Chompounoot; Linn, Aung Khine; Li, Hui-Chun; Thonabulsombat, Charoensri; Angsuthanasombat, Chanan (Protein and Peptide Letters, 2021)
Background: Mature lysostaphin ( 28-kDa Lss) from Staphylococcus simulans proves effective in killing methicillin-resistant Staphylococcus aureus (MRSA) which is endemic in hospitals worldwide. Lss is Zn2+-dependent endopeptidase, but its bacteriolytic activity could be affected by exogenously added Zn2+. Objective: To gain greater insights into structural and functional impacts of Zn2+and Ni2+on Lss-induced bioactivity. Methods: Lss purified via immobilized metal ion-affinity chromatography was assessed for bioactivity using turbidity reduction assays. Conformational change of metal ion-treated Lss was examined by circular dichroism and intrinsic fluorescence spectroscopy. Co-sedimentation assay was performed to study interactions between Zn2+-treated Lss and S. aureus peptidoglycans. Metal ionbinding prediction and intermolecular docking were used to locate an extraneous Zn2+-binding site. Results: A drastic decrease in Lss bioactivity against S. aureus and MRSA was revealed only when treated with Zn2+, but not Ni2+, albeit no negative effect of diethyldithiocarbamate—Zn2+-chelator on Lss-induced bioactivity. No severe conformational change was observed for Lss incubated with exogenous Zn2+ or Ni2+. Lss pre-treated with Zn2+ efficiently bound to S. aureus cell-wall peptidoglycans, suggesting non-interfering effect of exogenous metal ions on cell-wall targeting (CWT) activity. In silico analysis revealed that exogenous Zn2+, but not Ni2+, preferably interacted with a potential extraneous Zn2+-binding site (His253, Glu318 and His323) placed near the Zn2+-coordinating Lssactive site within the catalytic (CAT) domain. Conclusion: Our present data signify the adverse influence of exogenous Zn2+ ions on Lss-induced staphylolytic activity through the exclusive presence within the CAT domain of an extraneous inhibitory Zn2+-binding site, without affecting the CWT activity.
Keywords: peptidoglycan binding